Relevance of the TRIAP1/p53 axis in colon cancer cell proliferation and adaptation to glutamine deprivation - Nedara, Kenza; Reinhardt, Camille; Lebraud, Emilie; Arena, Giuseppe; Gracia, Céline; Buard, Valérie; Pioche-Durieu, Catherine; Castelli, Florence; Colsch, Benoit; Bénit, Paule; Rustin, Pierre; Albaud, Benoit; et al. (Frontiers in Oncology, 2022)
Human TRIAP1 (TP53-regulated inhibitor of apoptosis 1; also known as p53CSV for p53-inducible cell survival factor) is the homolog of yeast Mdm35, a well-known chaperone that interacts with the Ups/PRELI family proteins and participates in the intramitochondrial transfer of lipids for the synthesis of cardiolipin (CL) and phosphatidylethanolamine. Although recent reports indicate that TRIAP1 is a prosurvival factor abnormally overexpressed in various types of cancer, knowledge about its molecular and metabolic function in human cells is still elusive. It is therefore critical to understand the metabolic and proliferative advantages that TRIAP1 expression provides to cancer cells. Here, in a colorectal cancer cell model, we report that the expression of TRIAP1 supports cancer cell proliferation and tumorigenesis. Depletion of TRIAP1 perturbed mitochondrial ultrastructure, without a major impact on CL levels and mitochondrial activity. TRIAP1 depletion caused extramitochondrial perturbations resulting in changes in the endoplasmic reticulum-dependent lipid homeostasis and induction of a p53-mediated stress response. Furthermore, we observed that TRIAP1 depletion conferred a robust p53-mediated resistance to the metabolic stress caused by glutamine deprivation. These findings highlight the importance of TRIAP1 in tumorigenesis and indicate that the loss of TRIAP1 has extramitochondrial consequences that could impact on the metabolic plasticity of cancer cells and their response to conditions of nutrient deprivation.